Cover Picture: Discovery of Highly Potent Dual Orexin Receptor Antagonists via a Scaffold‐Hopping Approach (ChemMedChem 19/2016). (4th October 2016) - Heidmann, Bibia; Gatfield, John; Roch, Catherine; Treiber, Alexander; Tortoioli, Simone; Brotschi, Christine; Williams, Jodi T.; Bolli, Martin H.; Abele, Stefan; Sifferlen, Thierry; Jenck, François; Boss, Christoph
Abstract : The front cover picture shows the successful application of a scaffold‐hopping approach starting from the upper model structure and replacing the central core with different bicyclic diamine templates (some representative templates are depicted above the funnel). The structure–activity relationship optimizations (represented by the funnel and the arrows) of the high‐quality hits identified led to the successful discovery of a potent, orally bioavailable, and brain‐penetrant dual orexin receptor antagonist (DORA—bottom structure falling into the open hands) for the potential treatment of sleep‐related disorders. The head on the right side with closed eyes, as well as the starry sky, reminds us of sleep. More information can be found in the Full Paper by Bibia Heidmann, et al. onpage 2132 in Issue 19, 2016 (DOI:10.1002/cmdc.201600175 ).